Chorionic gonadotropin values in normal pregnancy - Rodríguez Gutierrez, Washington (2015)
The excretion of human chorionic gonadotropin (HCG) has been measured during normal pregnancy by using the hemagglutination technique of Wide and Gemzell. A total of 553 24 hr. urine collections were obtained from 425 pregnant women. The mean values for HCG presented a biphasic curve with a peak of 90.000 i.u. for the weeks 10- 12th., decreasing then gradually to a value of 30.000 and 21.000 i.u. in the 20th. and 30th. week respectively. A comparative study between the quantification of HCG in 24 hr. Urine collections and the morning sample calculated as an aliquot of one liter of urine did not show differences.